SORPTION RESISTANCE OF FICUS POLITA SEED POWDER AND CALCIUM CARBONATE FILLED POLYPROPYLENE - Shuaibu, M. A.; Hamza, P. A. P.; Hamza, A.; Isa, M. T. (FUDMA JOURNAL OF SCIENCES, 2020)
The aim of this research is to determine the influence of Calcium Carbonate and Ficus polita powder on the sorption resistance of Polypropylene Composites. The composites were prepared by mix melting and compression molding techniques. The compressed molded articles without and with fillers, PP, (PP/CaCO3) and (PP/FPSP) of different compositions (10/90, 20/80, 30/70, 40/60, 50/50, 60/40, 70/30 and 80/20) were characterized for, water absorption resistance capacity at the different fillers’ loading. Comparative studies were made on the sorption strength of the pure polypropylene (PP), polypropylene/calcium carbonate (PP/CaCO3) and polypropylene/ficus polita powder (PP/FPSP). The surface sorption characteristics of calcium carbonate and ficus polita powder has been investigated and the highest percentage was recorded at 20/80 of PP/FPSP (90%). There was gradual increase of the percentage sorption of water from unfilled polymer matrix to polymer composites. It was generally observed that for composition of 90/10, 80/20, 70/30, 60/40, 50/50 and 40/60 of both composites (PP/CaCO3 or PP/FPSP) as the filler’s loading, the % sorption of water also increases, with PP/FPSP having the least % sorption resistance (highest % of water absorbed). The sorption data for 20/80 and 30/70 PP/FPSP compositions showed large increase of the percentage of absorption of water. The PP and PP/CaCO3 composites have the best sorption resistance compared the pristine PP and PP/FPSP composites. Thus, it can be established, that, the PP with % sorption of 10 % water and 0.1 % in 0.1 M NaOH and 90 gPP/10 gCaCO3 with %sorption 0.1% in water and 0.1 M NaOH,